2008
DOI: 10.1063/1.2976767
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the origin of the internal rotational barrier for molecules with one rotatable dihedral angle

Abstract: Continuing our recent endeavor, we systematically investigate in this work the origin of internal rotational barriers for small molecules using the new energy partition scheme proposed recently by one of the authors ͓S. B. Liu, J. Chem. Phys. 126, 244103 ͑2007͔͒, where the total electronic energy is decomposed into three independent components, steric, electrostatic, and fermionic quantum. Specifically, we focus in this work on six carbon, nitrogen, and oxygen containing hydrides, CH 3 CH 3 , CH 3 NH 2 , CH 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 67 publications
5
55
0
1
Order By: Relevance
“…This result, meanwhile, confirms the validity of the Walsh rule. Also, this result is consistent with our other recent studies, [10][11][12][13][14][15][16][17][18][19][20][21][22][23] where we found that the electrostatic interaction is the major determinant in many chemical effects and processes such as bond rotation, and chemical reactions.…”
Section: Computational Detailssupporting
confidence: 93%
See 2 more Smart Citations
“…This result, meanwhile, confirms the validity of the Walsh rule. Also, this result is consistent with our other recent studies, [10][11][12][13][14][15][16][17][18][19][20][21][22][23] where we found that the electrostatic interaction is the major determinant in many chemical effects and processes such as bond rotation, and chemical reactions.…”
Section: Computational Detailssupporting
confidence: 93%
“…Notice that there is also a kinetic counterpart of the dynamic correlation effect, [29][30][31][32][33][34][35][36] This DFT approach to partition energies has been applied to a number of systems, such as conformational changes of small molecules, S N 2 reactions, chained and branched alkanes, and other systems. [10][11][12][13][14][15][16][17][18][19][20][21][22] Reasonably, good trends and linear relationships between theoretical and experimental scales of the steric effect have recently been observed by Taft at both group and entire molecular levels.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] In this work, we will examine the role of these quantities and relationships for a number of electrophilic aromatic substitution reactions. In particular, we are interested to see (i) what the performance of applying Hirshfeld charge and information gain in predicting the reaction barrier height of these reactions is; (2) whether the electrostatic component is still the dominant contributor to the barrier height; and (3) if there exist similar strong linear correlations from the information-theoretic quantities for these systems with transition state involved.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Some of these molecules are still seen through a classic model of lone pair and bond pair interactions. Therefore, accurate results are necessary [19] and are currently of great interest in the elucidation of the nature of the rotational barrier considering that many analysis of the rotational barriers are based on the decomposition of the electronic energy in orbitals, attractive, repulsive and quantum contributions, and steric effects [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%